A reduced maximality labeled transition system generation for recursive Petri nets. (November 2015) - Bouneb, Messaouda; Saidouni, Djamel; Ilie, Jean
Abstract In Saidouni et al. (Maximality semantic for recursive Petri net. Europeen conference on modelling and simulation (ECMS'13) pp 544–550, 2013) a maximality operational semantics has been defined for the recursive Petri net model. This operational semantics generates a true concurrency structure named maximality-based labeled transition systems (MLTS). This paper proposes an approach that generates an on-the-fly reduced MLTS modulo a maximality bisimulation relation. The interest of the approach is shown using an example concerning the woodshop cutting system.